Recovery of psychomotor function following general anaesthesia in children: a comparison of propofol and thiopentone/halothane - Schröter, Jens; Motsch, Johann; Hufnagel, A. R.; Bach, Alfons; Martin, Eike (Pediatric anesthesia, 1996)
The present study was undertaken to compare immediate recovery and recovery of complex psychomotor function in 20 children (aged 6-12 years) following general anaesthesia with either thiopentone/halothane or propofol. Early recovery of psychomotor skills was significantly faster in the propofol group than in the thiopentone/halothane group. Compared to preanaesthesia baseline the sedation and cooperation scores, the reaction time to visual and auditory stimuli as well as the postbox test and the flicker fusion frequency were less impaired after propofol than after thiopentone/halothane anaesthesia up to 120 min postoperatively. In the propofol group most tests reached preanaesthesia levels after 120 min, while in the thiopentone/halothane group these levels were not reattained throughout the entire study period. The results indicate that the recovery of psychomotor function in paediatric patients following general anaesthesia with propofol is significantly faster than with thiopentone/halothane. This has important implications for parental satisfaction, the time over which patients need to be monitored in the recovery room and for the discharge criteria after daycase surgery.